Empowerment PKK mothers in Teluk Majelis Village through Assistance in Increasing Production and Digital Marketing Sweet and Sour Pedada Fruit - Permana, Edwin (Edumedia Solution, 2025)
Pedada fruit is one of the mangrove fruits in Teluk Majelis village. This fruit has a fairly sour taste but is rich in vitamin C. PKK mothers tried to make this fruit into candy. However, this product still has many shortcomings such as taste and shape, no product legality, no social media marketing and web marketing, and no attractive packaging. This is the reason the team helped PKK mothers in Teluk Majelis village improve the product. The outputs of this service, such as improving product quality, website development, and digital marketing training, showed a significant positive impact on PKK mothers and the surrounding community. This not only increased their income, but also strengthened their brand image and business professionalism. This success reflects the great potential of community empowerment through the development of local products and appropriate digital technology